Tanah runtuh di Malaysia : "Geobencana" atau "Geobahaya" - Hamzah Hussin; Sarah Aziz Abdul Ghani; Tajul Anuar Jamaluddin; Mohammad Khairul Azhar Abdul Razab (2015)
Landslide is a natural process that is common in hilly areas, whether natural hills or areas